Immune checkpoints and cellular landscape of the tumor microenvironment in non-melanoma skin cancer (NMSC) - Mousa, Ahmed M.; Enk, Alexander; Hassel, Jessica C.; Reschke, Robin Niklas (Cells, 2024)
Non-melanoma skin cancer (NMSC) is primarily categorized into basal cell carcinoma (BCC), the most prevalent form of skin cancer, and cutaneous squamous cell carcinoma (cSCC), the second most common type. Both BCC and cSCC represent a significant health burden, particularly in immunocompromised individuals and the elderly. The immune system plays a pivotal role in the development and progression of NMSC, making it a critical focus for therapeutic interventions. This review highlights key immunological targets in BCC and cSCC, with a focus on immune checkpoint molecules such as PD-1/PD-L1 and CTLA-4, which regulate T cell activity and contribute to immune evasion. This review also highlights anti-tumor immune cell subsets within the tumor microenvironment (TME), such as tumor-infiltrating lymphocytes (TILs) and dendritic cells. Additionally, it examines the immunosuppressive elements of the TME, including regulatory T cells (Tregs), myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), and cancer-associated fibroblasts (CAFs), as well as their roles in NMSC progression and resistance to therapy. Emerging strategies targeting these immune elements, such as monoclonal antibodies, are also discussed for their potential to enhance anti-tumor immune responses and improve clinical outcomes. By elucidating the immunological landscape of BCC and cSCC and drawing comparisons to melanoma, this review highlights the transformative potential of immunotherapy in treating these malignancies.
Gesehen am 31.03.2025